95.7k views
5 votes
Whats the answer and how do i get the answer myself

Whats the answer and how do i get the answer myself-example-1
User Maddesa
by
6.1k points

1 Answer

7 votes

Answer:


f^(-1) (x) =  (x)/(3)  - 3

Explanation:

Let here the given function f(x) = y

or,
x= f^(-1) (y)

y = 3x+ 9

Now, solving for x, we get

3x+ 9 = y ⇒ 3x = y - 9

or,
x = (y-9)/(3) = (y)/(3)  - (9)/(3)


x = ( (y)/(3))  - 3

Now, substituting x and y

Hence,
f^(-1) (x) =  (x)/(3)  - 3

User Mark Lagendijk
by
6.6k points